External genital endometriosis: treatment and rehabilitation - A. G. Solopova; E. E. Achkasov; V. S. Moskvichyova; E. Grigorevskaya; D. M. Ampilogova (IRBIS LLC, 2021)
Aim: to systematize the data on rehabilitation methods and management tactics for women with external form of genital endometriosis.Materials and Methods. We searched for publications in the international scientific databases: scientific electronic library eLibrary, Scholar, ScienceDirect, Cochrane Library, PubMed/MEDLINE released for the last 5 years. The data on the current approach to the therapy and rehabilitation of women with external genital endometriosis are presented in the study. Search queries in Russian and English were used as follows: «endometriosis», «rehabilitation», «gynecology», «quality of life».Results. Endometriosis is considered an independent risk factor for the development of malignant tumors not only targeting the reproductive system, but also affecting large intestine, bladder, and mammary glands. Moreover, such patients often suffer from emotional and psychosexual disorders as well as impaired socialization. Special attention should be paid to diagnostics of disease relapses to avoid potential malignant transformation of endometrioid tissue. We also provide a current view on the treatment and rehabilitation of women with external genital endometriosis. Endometriosis is a polyetiological disease that can be manifested as dysmenorrhea, dyspareunia, chronic pelvic pain, as well as dysuria and dyschesia upon affecting adjacent organs in the pathological process. Finally, we provide insights into potential therapeutic approaches for solving such manifestations.Conclusion. It is necessary not only to conduct a combination treatment, but also develop personalized rehabilitation programs allowing to improve the quality of patient life as well as create comfortable conditions for social adaptation of women with endometriosis.